Negotiating glocalization - Bhaduri, Saugata. (ed.) (London, 2008)
About the Book: Negotiating Glocalization: Views from Language, Literature and Culture Studies This volume attempts to negotiate 'glocalization'- where the 'global' and the 'local' become partners in a hybrid game of mutual interpellation- through the fields of language, literature and culture. Unlike erstwhile modes of imperialism where the centre that wielded power would often monologically digest the periphery into submission, globalization seems to work primarily by implicating the local in its processes, leading to what Japanese business processes called in the 1980s, and what Roland Robertson introduced to the Anglophobic academia in the 1990s, 'glocalization', where, rather than being two binaries at loggerheads, the 'global' and the 'local' become partners in a hybrid game of mutual interpellation. While there should be no illusion that this implication of the local in the globalizing process is not necessarily a victory of the local, but rather its strategic co-optation by the forces of globalization, a question arises as to how this co-optation can be negotiated. Interestingly, structures of information, knowledge and discourse dissemination being the driving forces behind contemporary 'glocalization', it appears that studies in the fields of language, literature and culture may provide important loci for such attempts at 'negotiating glocalization'. It is with this view that this volume showcases twelve articles, four each from the three areas mentioned above, which all try to provide possible attempts at such a negotiation. Evidently, the volume does not claim to provide definitive answers to the complex question it presupposes, but it does pose some pointers in the way towards this task of negotiating the current times. Contents Acknowledgements List of Contributors Introduction The Global, the Local and the Role of Language-Literature-Culture Studies Today SECTION 1: GLOCALIZATION AND CULTURE STUDIES OF MULTICULTURALISM AND THE NEW MEDIA Education
Keywords: Glocalization